(untitled) (Update Dental College Journal, 2016)
Background The study was conducted to know the prevalence & pattern of dental health problems among Bangladeshi people. Methods It was a descriptive type of cross sectional study conducted in Department of Orthodontics & Dentofacial Orthopaedics of Dhaka Dental College & Hospital, Dhaka Purposive sampling technique was followed and a close ended questionnaire was utilized for face to face interview with the respondents from September2011 toFebruary2012. Results This was a cross sectional study conducted among 500 patients in the department of Orthodontics and Dentofacial Orthopaedics, Dhaka Dental College and Hospital. Gingivitis is the commonest problem in Bangladeshi people according to present study. The second most dental problem was dental caries. The prevalence of orthodontic problems was comparable to the observations made by others. Males and females are equally affected with slight variations in the nature of problems among both genders. Conclusion Good oral health is essential to improve individual overall health & well-being. We urge to take this information & use it for program planning & advocating for the health of patients, specially for the patients who will receive orthodontic treatment. Therefore, current orthodontic students should receive more education & training before the management of malocclusion to improve the overall quality of care for orthodontic patients. Update Dent. Coll. j: 2015; 5 (2): 01-08